Social Participation of a Fishing Community in the Coastal Region of Bontosua Island - Sakaria To Anwar; Ridwan Syam; Muhammad Taurid Yahya (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
The fishing community of Bontosua Island experienced very basic social changes, the intensive changes were at least influenced by two aspects, namely, the decreasing level of social participation and the entry of market penetration which also affected the existing pattern of life and social order. The main subject of the uncertain life pattern of the island fishing community is the increasingly sparse level of Social Participation experienced by the community. The approach used in this study is a combination of qualitative and quantitative methods (questionnaire) to describe the social participation of fishing communities in the coastal area of the village. The methods used in the data collection process were in-depth interview techniques, questionnaires, and observation. The primary data of this study amounted to 16 respondents. The results indicate that the fishing community tends to be "eroded" in the fields of religion and mutual cooperation. Therefore, it is hoped that the Bontosua fishing community will increase the level of social participation, especially in the fields of religion and mutual cooperation to create an atmosphere of integration and equilibrium at all levels of society.